Association analysis of HTR6 and HTR2A polymorphisms in sporadic Alzheimer's disease - Thome, Johannes; Retz, Wolfgang; Baader, Miriam; Pesold, B.; Hu, Mei; Cowen, M.; Durany, N.; Adler, G.; Henn, Fritz A.; Rösler, Michael (Journal of neural transmission, 2001)
In order to identify gene variants related to the serotonergic neurotransmitter system that possibly represent a hereditary risk factor for sporadic Alzheimer's disease (AD), patients suffering from AD and non-demented psychiatric inpatients without symptoms of dementia were genotyped for polymorphisms of HTR6 (267C/T) and HTR2A (−1438G/A). Although there was a tendency toward an increased number of the genotype TT of the 5-HT6 receptor polymorphism in AD patients when compared to controls (2.8% vs. 1.3%), neither this nor the 5-HT2A promoter polymorphism showed significant differences in their genotypic or allelic distribution among patients and controls. These polymorphisms probably do not represent major genetic risk factors of AD. However, further studies including other genetic variants of the serotonergic neurotransmitter system are needed in order to elucidate their role in AD.